ACCOUNTABILITY OF CIVIL CIVIL APPARATUS PERFORMANCE IN THE DEPARTMENT OF EDUCATION AND CULTURE OF WEST KALIMANTAN PROVINCE - Nining Andriani (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The problem in this research includes the still low level of ASN compliance in compiling and reporting Employee Performance Targets. The purpose of this study is to describe and analyze the performance measurement of civil servants at the Education and Culture Office of West Kalimantan Province, seen from the aspects of: Accountability, Responsibility, and Responsiveness. The results of the study indicate that Accountability, Responsibility, and Responsiveness are key elements in reflecting the quality of civil servant performance at the Education and Culture Office of West Kalimantan Province. However, in its implementation, these three aspects have not been running optimally. ASN accountability is still hampered by a lack of discipline in reporting and minimal transparency of work results. Responsibility is also not fully reflected in ASN's commitment to carrying out duties and responsibilities professionally. On the other hand, responsiveness to community needs, especially in the fields of education and culture, is still relatively slow, which indicates a lack of active involvement of ASN in absorbing and responding to public aspirations quickly and appropriately. This research recommends strategic steps to strengthen accountability through a more structured and regularly monitored performance reporting system. Improving accountability can be achieved through ongoing development, professional ethics training, and consistent enforcement of work discipline. To enhance responsiveness, a more participatory and adaptive public service mechanism needs to be developed to meet community needs.